2003
DOI: 10.1016/s0925-4439(02)00227-2
|View full text |Cite
|
Sign up to set email alerts
|

Anti-apoptotic proteins are oxidized by Aβ25–35 in Alzheimer's fibroblasts

Abstract: We have examined the effects of the beta-amyloid peptide (Abeta(25-35)) on fibroblasts derived from subjects with Alzheimer's disease (AD) and from age-matched controls. The peptide was significantly more cytotoxic to the AD-derived fibroblasts. The level of protein oxidation was also greater in the cells from AD subjects. Two-dimensional electrophoresis (2-DE) coupled with immunostaining for protein carbonylation revealed specific oxidation-sensitive proteins (OSPs) in both the control and AD-derived cells. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 33 publications
0
49
0
Order By: Relevance
“…The expression of HSP60 is significantly decreased in AD (Yoo et al, 2001). Also Aβ(25-35) induces oxidation of HSP60 in fibroblasts derived from AD patients (Choi et al, 2003). Taken together, oxidation of HSP60 is likely caused by the abnormal accumulation of Aβ.…”
Section: Oxidatively Modified Proteins By Aβ(1-42) In Vivomentioning
confidence: 91%
“…The expression of HSP60 is significantly decreased in AD (Yoo et al, 2001). Also Aβ(25-35) induces oxidation of HSP60 in fibroblasts derived from AD patients (Choi et al, 2003). Taken together, oxidation of HSP60 is likely caused by the abnormal accumulation of Aβ.…”
Section: Oxidatively Modified Proteins By Aβ(1-42) In Vivomentioning
confidence: 91%
“…In general, however, only subsets of proteins have been shown to be carbonylated, such as chaperones, cytoskeletal proteins, protein disulfide isomerases (PDIs), and various metabolic enzymes (1,5,7,34). Oxidation of these proteins, many of which are cell protective, may trigger downstream events such as UPR and apoptosis.…”
Section: Introduction Nmentioning
confidence: 99%
“…In support of the neuroprotective effects of Hsp60, it has been demonstrated that in a human neuroblastoma cell line, induced expression of the chaperonin prevented intracellular -amyloid-induced inhibition of complex IV and consequently reduced apoptosis [84]. A 25-35 induced oxidation of Hsp60 in fibroblasts derived from AD patients [85] and, also, Hsp60 was oxidized by A 1-42 leading to a loss of function of the chaperonin, which caused an increase in protein misfolding and aggregation [86]. Again, this would be a chaperonopathy by defect.…”
Section: Hsp60mentioning
confidence: 96%